Decreased cerebrospinal fluid amyloid beta (1–40) levels in frontotemporal lobar degeneration. Issue 7 (19th March 2007) - Pijnenburg, Y A L; Schoonenboom, S N M; Mehta, P D; Mehta, S P; Mulder, C; Veerhuis, R; Blankenstein, M A; Scheltens, P
Abstract : The role of amyloid metabolism in the pathophysiology of frontotemporal lobar degeneration (FTLD) has yet to be elucidated. We compared CSF levels of amyloid beta 1–40 (Aβ40) and amyloid beta 1–42 (Aβ42) in patients with FTLD (n = 21) versus patients with Alzheimer's disease (AD, n = 39) and in control subjects (n = 30). While in AD cases Aβ42 levels were lower and CSF Aβ40 levels equal to those in controls, a significant decrease in Aβ40 and increase in the CSF Aβ42/Aβ40 ratio was observed in FTLD compared with AD and control subjects. These findings favour a differential involvement of amyloid β peptides in FTLD compared with AD.